Incorporation of coconut shell based nanoparticles in kenaf/coconut fibres reinforced vinyl ester composites. (15th March 2017) - H P S, Abdul Khalil; Masri, M; Saurabh, Chaturbhuj K; Fazita, M R N; Azniwati, A A; Sri Aprilia, N A; Rosamah, E; Dungani, Rudi
Abstract: In the present study, a successful attempt has been made on enhancing the properties of hybrid kenaf/coconut fibers reinforced vinyl ester composites by incorporating nanofillers obtained from coconut shell. Coconut shells were grinded followed by 30 h of high energy ball milling for the production of nanoparticles. Particle size analyzer demonstrated that the size of 90% of obtained nanoparticles ranged between 15–140 nm. Furthermore, it was observed that the incorporation of coconut shell nanofillers into hybrid composite increased water absorption capacity. Moreover, tensile, flexural, and impact strength increased with the filler loading up to 3 wt.% and thereafter decrease was observed at higher filler concentration. However, elongation at break decreased and thermal stability increased in nanoparticles concentration dependent manner. Morphological analysis of composite with 3% of filler loading showed minimum voids and fiber pull outs and this indicated that the stress was successfully absorbed by the fiber.